Considering Local Government Policies Related to Madrasah Diniyah Takmiliyah in Indonesia - Ashari, Muhammad Khakim; Faizin, Moh; Yudi, Usman; Aziz, Yahya; Irhamni, Hadi; Athoillah, Sukijan (Pascasarjana Universitas KH. Abdul Chalim, 2023)
The implementation of madrasah diniyah takmiliyah (MDT) is very dynamic in its history, established before this country was not born until now it still exists in the midst of community life and has contributed a lot to the nation as an institution that concentrates on Islamic studies. Although it has been established for a long time, madrasah diniyah has only recently received recognition from the government through the issuance of Law No. 20 of 2003 concerning the national education system and also the issuance of Government Regulation No. 55 of 2007 concerning religious education and religious education. This study examines local government policies related to the implementation of madrasah diniyah takmiliyah as part of the implementation of these two government policies. This study uses a systematic literature review (SLR) approach, which is a method used to identify, verify and classify relevant data findings into discussion themes. The result of this study is that the policies that have been established by the government have not fully guaranteed the vital role of the government (central and local) towards the implementation of education in madrasah diniyah, the lack of government attention is one of the reasons for the lack of development of MDT until now. In some regions, there is a policy to integrate MDT into formal schools, this aims to increase the role and existence of MDT and affirm its role as an Islamic educational institution that produces religious and characterized graduates.